Simple discrete bit-loading for OFDM systems in power line communications - Al-Mawali, K S; Sadik, A Z; Hussain, Z M (2011 IEEE International Symposium on Power Line Communications and Its Applications, 2011)
Adaptive bit-loading algorithms can improve the performance of OFDM systems significantly. The tradeoff between the algorithms performance (optimum solution) and the computational complexity is essential for implementation of loading algorithms. In this paper, we present a low complexity non-iterative discrete bit-loading algorithm to maximize the data rate subject to specified target BER and uniform power allocation. Simulation results show that the proposed algorithm outperforms the equal-BER loading and achieves similar rates to incremental allocation, yet with much lower complexity.